Cardiac output and peripheral vascular resistance during normotensive and hypertensive pregnancy – a systematic review and meta‐analysis. (6th April 2021) - Mulder, EG; de Haas, S; Mohseni, Z; Schartmann, N; Abo Hasson, F; Alsadah, F; van Kuijk, SMJ; van Drongelen, J; Spaanderman, MEA; Ghossein‐Doha, C
Abstract : Background: In‐depth insight into haemodynamic changes during normotensive pregnancy may help identify women at risk for gestational hypertensive complications. Objectives: To determine the magnitude of changes in cardiac output and its determinants stroke volume and heart rate, and total peripheral vascular resistance during singleton normotensive and hypertensive pregnancies. Search strategy: PubMed (NCBI) and Embase (Ovid) databases were searched from their inception up to November 2019. Selection criteria: Studies reporting original measurements of haemodynamic parameters during pregnancy together with a non‐pregnant reference measurement. Studies including women using antihypertensive medication were excluded. Data collection and analysis: Pooled mean differences between pregnant and non‐pregnant women, and absolute values of haemodynamic parameters were calculated for predefined gestational intervals using a random‐effects model in normotensive and hypertensive pregnancy. Meta‐regression analysis was used to analyse group differences in adjustments and absolute values during pregnancy. Main results: In normotensive pregnancies, cardiac output increased from the first weeks on, reaching its highest level early in the third trimester (mean difference, 1.41 l·min 1 ; 95% CI 1.18–1.63 l·min). In parallel, vascular resistance decreased progressively until its nadir in the early third trimester (mean difference, −331 dyn·sec –1 ·cm –5 ; 95% CI −384 to −277 dyn·sec –1 ·cm –5 ) and then increased slightly at term. In hypertensive pregnancies, the initial cardiac output increase was higher and vascular resistance did not change throughout gestation compared with reference values. Conclusions: Hemodynamic changes in women who eventually develop hypertensive complications are substantially different. Serial monitoring and plotting against developed normograms can identify women at risk and may allow timely intervention. Tweetable abstract: Monitoring haemodynamic changes in pregnancy helps identify women at risk for hypertensive complications. Tweetable abstract: Monitoring haemodynamic changes in pregnancy helps identify women at risk for hypertensive complications.